Optimum Conditions for Mutacin Production From Streptococcus mutans S2 - Salih, Aya R; Jasim, Hameed M; Risan, Mohsan H (Al-Nahrain Journal of Science, 2018)
Mutacin production by Streptococcus mutans S2 was detected by inoculating production medium (Brain Heart Infusion broth supplemented with yeast extract 2% (w/v) and CaCO3 1% (w/v)) with fresh culture of the bacterial isolate. The inhibitory effect of mutacin produced by S. mutans S2 was studied by detection the inhibitory effect of mutacin against the test microorganism (Streptococcus pyogenes) grown on BHI agar plates. Optimum conditions for mutacin production from S. mutans S2 includes optimum carbon, nitrogen and phosphate sources and their concentrations, optimum temperature and pH. were studied. Results showed that these conditions include the supplementation of the production medium (Brain-Heart Infusion broth containing 1%CaCO3) with sucrose as a sole source for carbon and energy at a concentration of 3%, and yeast extract as a nitrogen source at a concentration of 2%, and KH2PO4 as a phosphate source at a concentration of 0.5%, with initial medium pH of 7, then inoculating with fresh culture (OD 0.8), and incubation at 37°C for 24 hours in candle jar. Under these conditions the maximum mutacin production S. mutans S2, causing maximum inhibition effect against test microorganism (S. pyogenes) reached 35 mm in diameter.Fu